2011
DOI: 10.1111/j.1746-1049.2011.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Firm Productivity and Investment Climate in Developing Countries: How Does Middle East and North Africa Manufacturing Perform?

Abstract: Firm productive performances in five Middle East and North African (MENA) economies and eight manufacturing industries are compared to those in 17 other developing countries. Although the broad picture hides some heterogeneity, enterprises in MENA often performed inadequately given the middle-income status of the MENA economies, with the exception of Morocco and, to some extent, Saudi Arabia. Firm competitiveness is a more constant constraint, with a unit labor cost higher than in most competitor countries, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 75 publications
0
40
0
1
Order By: Relevance
“…However, most of the previous evidences supported a positive relation between these two variables. Kinda et al [58] studied the relationship between investment climate and firm productivity in the Middle East and North Africa and showed that the cost and access to finance lead to firm performance discrepancies. Fernandes [66] and Biesebroeck [67] found a positive link between access to overdraft facilities and firm TFP and a negative association between bank loan accessibility and firm TFP in Bangladesh and in several African countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the previous evidences supported a positive relation between these two variables. Kinda et al [58] studied the relationship between investment climate and firm productivity in the Middle East and North Africa and showed that the cost and access to finance lead to firm performance discrepancies. Fernandes [66] and Biesebroeck [67] found a positive link between access to overdraft facilities and firm TFP and a negative association between bank loan accessibility and firm TFP in Bangladesh and in several African countries.…”
Section: Discussionmentioning
confidence: 99%
“…In all estimations, we also included the firm-specific factors (characteristics of the firm itself) and external environment factors that affected firms' economic performance. The benchmark for selecting these firm specific and investment climate variables follows the studies of Giang et al [30], Bastos and Nasir [55], Escribano and Guasch [56], Dollar et al [57], and Kinda et al [58]. To be more specific, we imposed a set of firm-specific variables: firm size, age, and export.…”
Section: Datamentioning
confidence: 99%
“…Moretti, 2004, van Biesebroeck, 2005, Foster et al, 2008, Nichter and Goldmark, 2009, Bloom and van Reenen, 2010, Ali and Peerlings, 2011, Amin, 2011, Kinda et al, 2011, Martin et al, 2011, Saliola and Seker, 2011, Rijkers and Costa, 2012, Bloom et al, 2013). Only a few studies have analyzed enterprise performance in sub-Saharan Africa.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, the elasticity of the production to the inputs in the Cobb-Douglas is easier to interpret than in translogarithmic production. To be more specific, the translog technology generally suffers from a collinearity problem among the regressors (Kinda et al 2011). Thus, in this study, we assumed that production technology followed Cobb-Douglas production functions.…”
Section: Measurement Of Firm Productivitymentioning
confidence: 99%